Bladder recurrence after surgery for upper urinary tract urothelial cell carcinoma: Frequency, risk factors, and surveillance - Azémar, Marie-Dominique; Comperat, Eva; Richard, François; Cussenot, Olivier; Rouprêt, Morgan (Urologic oncology, 2011)
To highlight the main risk factors for metachronous bladder recurrence after treatment of an upper urinary tract urothelial cell carcinomas (UUT-UCCs) based on the recent literature. Data on urothelial malignancies after UUT-UCCs management in the literature were searched using MEDLINE and by matching the following key words: urinary tract cancer; bladder carcinomas, urothelial carcinomas, upper urinary tract, renal pelvis, ureter prognosis, carcinoma, transitional cell, renal pelvis, ureter, bladder cancer, cystectomy, nephroureterectomy, minimally invasive surgery, recurrence, and survival. No evidence level 1 information from prospective randomized trials was available. A range of 15% to 50% of patients with a UUT-UCC will subsequently develop a metachronous bladder UCC. Intraluminal tumor seeding and pan-urothelial field change effect have both been proposed to explain intravesical recurrences. In most cases, bladder cancer arises in the first 2 years after UUT-UCC management. However the risk is lifelong and repeat episodes are common. The identification of variables that allow accurate risk stratification of UUT-UCC patients with regards to future bladder relapse is disappointing. No factors have been identified to date that can reliably predict bladder recurrences. A history of bladder cancer prior to UUT-UCC management and upper tract tumor multifocality are the only frequently reported clinical risk factors among current literature. Prior histories of bladder cancer and upper tract tumor multifocality are the most frequently reported risk factors for bladder tumors following UUT-UCCs. Surveillance regimen is based on cystoscopy and on urinary cytology for at least 5 years.